Ethics and leadership from the perspective of university students and professionals - Mercader Pomarón, Víctor Manuel (Journal of Management and Business Education, 2020)
This research is focused on determining and analyzing the need and the relationship of Ethics and Leadership from the perspective of professionals and university students while obtaining the resulting parameters of respective measurement to use in favor of business and organizational improvement. Additionally, it reveals the way in which professionals behave and apply ethical values through the applied instrument, when they perform in leadership roles, thus achieving results and metrics that have not been previously found with so many values and indicators in the extensive literature analyzed. This empirical study is complemented by the review and analysis of literature where the dimensions of ethics and leadership are related, as well as those associated to education, obtaining indicators that were the basis for the development of new theoretical categorizations. A quantitative instrument was applied with two similar samples, but with different types of participants, one consisting of 436 professionals and the other one of 371 university students; obtaining results with the respective metrics and from there, the descriptive statistical analysis, Anova and correlations that show high significance when relating ethics and leadership and the perception of professionals and students. This study is considered of total relevance and helps businessmen, entrepreneurs, directors and employees, as well as students, teachers, leaders, professionals and human beings in general, to be better prepared as leaders and to analyze and find solutions for ethical and productive achievements. If every company, organization, educational institution and society exercised its leadership based on ethics, the results and achievements generated would not harm humanity and would benefit everyone.